The Impact of Inflation, Interest Rates, Exchange Rates, and Money Supply on IHSG - Yesa Cahayaning Ramadhani; Ari Kartiko; Ella Mayasari (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research was motivated by the Composite Stock Price Index (IHSG), which at that time experienced fluctuations up and down in line with economic and political activity. At that time, fluctuations in joint stock prices were caused by macroeconomic factors, one of which was inflation, increases in interest rates, foreign exchange rates, money supply, and others. These macroeconomic factors greatly influence the performance of the Composite Stock Price Index (IHSG), especially accompanied by the emergence of Covid-19 which has had a very negative impact on the entire Indonesian economy. This research aims to determine the effect of inflation, interest rates, exchange rates, and money supply on the composite stock price index (IHSG) during the COVID-19 pandemic. This research uses a quantitative approach with an associative type of research. The research data used is secondary data with Indonesian research samples in the 2018-2022 period. The analysis technique used is multiple linear analysis using SPSS 25. From the research results, it can be concluded that partially this research shows that the variables inflation, interest rates, and money supply each have a positive and significant effect on the composite stock price index (IHSG). Meanwhile, the exchange rate variable negatively and significantly affects the composite stock price index (IHSG). Meanwhile, the variables inflation, interest rates, exchange rates, and money supply simultaneously positively and significantly influenced the composite stock price index (IHSG) during the 2018-2022 Covid pandemic.